Arts, Humanities, and Social Sciences: A Scoping Review of Uncited Research - Samah, Tawil; Nada, Khaddage-Soboh (SAGE open, 2024)
The goal of this bibliometric analysis is to summarize publications on the contributions of a higher education university in arts, humanities, and social sciences and evaluate their citation status. Ninety-one publications were indexed in Scopus and WOS databases between 2018 and 2022. All publications appeared in 69 different journals, books, and conferences. About 51.6% of all studies were single-authored. The median number of publications per author was 27.01 ± 48.0 and that of citations was 223.0 ± 764.0. Positive correlations were observed between the journal’s CiteScore and authors’ count with citation number (r2 = .625 and .207 respectively; p < .005). Publications written by ≥3 authors with international collaboration received the maximum number of citations (p < .005). Moreover, the mean number of citations for publications written by associate or assistant professors was significantly higher than those composed by their peers (p = .033). Defining the field of arts and humanities remains a difficult exercise, because of its blurry theoretical background. Thus, a repetitive evaluation of its current status remains essential. Plain Language Summary The objective of this study was to summarize publications on the contributions of the Lebanese American University in arts, humanities, and social sciences and evaluate their citation status. Methods: 91 publications indexed in Scopus and WOS databases were included. All publications appeared in 69 different journals, books, and conferences. A Positive correlation was observed between the journal’s reputation and citation number. Limitations: Other publications might have been published during the redaction of this review but were not included. Only the WoS and Scopus databases were searched for the inclusion of the publications which could have hide other relevant publications. The novelty of this review is the provision of data that is known to be the least cited type of research. Implications: Despite that this field is regarded as ambiguous thus less attractive, it remains an important subject of study and warrants further consideration.